2021
DOI: 10.21203/rs.3.rs-138436/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serum Calprotectin (S100A8/A9): A Promising Biomarker in Diagnosis and Follow-up in Different Subgroups of Juvenile Idiopathic Arthritis

Abstract: IntroductionIn the management of juvenile idiopathic arthritis (JIA), there is a lack of diagnostic and prognostic biomarkers. This study assesses the use of serum calprotectin (sCal) as a marker to monitor disease activity, and as a classification and prognosis tool of response to treatment or risk of flares in patients with JIA. MethodsEighty-one patients with JIA from the CAP48 multicentric cohort were included in this study, as well as 11 non-pediatric healthy controls. An enzyme-linked immunosorbent assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…In a recent study by Darwish et al [41]They observed that MSUS is extremely sensitive for early diagnosis of joint involvement in JIA when compared to physical examination, since MSUS identified more synovitis than clinical examination (subclinical synovitis). n agreement with C line a et al [35] active illness was associated with serum calprotectin levels that were more than twice as high as those seen in individuals whose disease was in remission (6555ng/mL vs. 11403ng/mL), demonstrating a strong correlation between disease activity and calprotectin levels.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In a recent study by Darwish et al [41]They observed that MSUS is extremely sensitive for early diagnosis of joint involvement in JIA when compared to physical examination, since MSUS identified more synovitis than clinical examination (subclinical synovitis). n agreement with C line a et al [35] active illness was associated with serum calprotectin levels that were more than twice as high as those seen in individuals whose disease was in remission (6555ng/mL vs. 11403ng/mL), demonstrating a strong correlation between disease activity and calprotectin levels.…”
Section: Discussionsupporting
confidence: 90%
“…Methotrexate continues to be the most extensively used traditional DMARD for the treatment of JIA due to its efficacy in disease control and tolerable toxicity. n agreement with aC line et al [35] and Frosch et al [6]who revealed that the blood level of calprotectin in JIA patients was significantly higher than in the control group. These findings are consistent with the physiological explanation that calprotectin is an acute phase reactant that is typically expressed by monocytes, granulocytes, and macrophages in an early differentiation stage, following their activation by damage-associated molecular patterns (DAMPs) as a result of inflammation [36,37].CLP is accountable for leukocyte motility and trafficking, as well as inflammation amplification.…”
Section: Discussionsupporting
confidence: 89%
“…This highlights the utility of P-MRP8/14 as a tool for disease activity in patients with newly-onset JIA. Moreover, in a recent study, La et al found that S-MRP8/14 has more specificity than CRP does as a diagnostic tool and marker of disease activity for JIA [25].…”
Section: Discussionmentioning
confidence: 99%
“…S100 proteins may activate innate immune cells, predominantly monocytes and macrophages, upon binding the RAGE receptor or TLR4 by enhancing the secretion of proinflammatory molecules (187). High concentrations of S100 proteins (both S100A8/A9 and S100A12) are measured in patients with sJIA and therefore these molecules were proposed to be biomarkers (188)(189)(190)(191)(192)(193)(194)(195). The release of IL-1 and other inflammatory cytokines by total white blood cells (WBCs) or monocytes from sJIA patients was reduced upon depleting serum S100A8/A9 or by preventing the S100A12 complex formation (191,196,197).…”
Section: How Neutrophilia May Fuel the Pathogenesis Of Sjiamentioning
confidence: 99%